Emission control in quasi-bound states in the continuum and monolayer WS2/Si3N4 hybrid metasurfaces - Bradley, Louise; Zhang, Yongliang; Jia, Na; Dobie, Jack Scott-Telford (My University, 2025)
Si3N4 slotted disk metasurfaces with a high Q-factor have been designed and fabricated. Experimental measurements show enhanced emission from monolayer WS2 – metasurface system. A Rabi splitting energy of 33.55 meV is achieved in the simulation.
Novel Optical Materials and Applications 2025
PUBLISHED
Marseille France